2017
DOI: 10.1021/acs.joc.7b01019
|View full text |Cite
|
Sign up to set email alerts
|

Pathways in the Degradation of Geminal Diazides

Abstract: The degradation of geminal diazides is described. We show that diazido acetates are converted into tetrazoles through the treatment with bases. The reaction of dichloro ketones with azide anions provides acyl azides, through in situ formation of diazido ketones. We present experimental and theoretical evidence that both fragmentations may involve the generation of acyl cyanide intermediates. The controlled degradation of terminal alkynes into amides (by loss of one carbon) or ureas (by loss of two carbons) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 63 publications
3
16
0
Order By: Relevance
“…A similar formation of a nitrile species was recently observed by us in the ring‐opening of 3,3‐diazidooxindoles under basic conditions . In the related fragmentation of diazidated 1,3‐dicarbonyls, we also proposed the existence of nitrile intermediates (i.e., cyanoformates), mainly based on calculations, although the reaction conditions did not allow for the isolation of the nitriles in those cases.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…A similar formation of a nitrile species was recently observed by us in the ring‐opening of 3,3‐diazidooxindoles under basic conditions . In the related fragmentation of diazidated 1,3‐dicarbonyls, we also proposed the existence of nitrile intermediates (i.e., cyanoformates), mainly based on calculations, although the reaction conditions did not allow for the isolation of the nitriles in those cases.…”
Section: Resultssupporting
confidence: 69%
“…We also present our results on the fragmentation of the diazides 6 when treated with amines: Besides the expected amides 7 , we isolated aromatic nitriles 8 in good yields. Since the existence of nitrile intermediates in the course of the fragmentation of diazido compounds was mostly a postulate by us in previous reports, primarily based on calculations, the current study provides experimental support for our mechanistic view on the amine‐triggered fragmentation of diazides.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…[10] During ouro ngoing studieso nt he synthesis [11] andr eactivity [12] of compoundsw ithg eminal diazidou nits,w eo bserved that tetrazolef ormationc an be easilyt riggered with this still barely knownc ompoundc lass: [13,14] Diazidoe sters( e.g., 1)w ere smoothly convertedi ntot he correspondingt etrazolest hrough simple treatment with triethylaminea sb asea dditive (Scheme2A). [15] We then questioned whetherau niversal approach to thetetrazole core maye xist,startingfromgeminal diazides ubstrates, andd eliberatelyd ifferent from thec lassical cycloadditionw ithn itrilesa nd azides.I ndeed, ourl iteratures earch revealed that afew examples forthe conversion of diazidocompounds into tetrazolesw erer eported: Fore xample,t he thermal decompositiono fd iazidodiphenylmethane 3 into tetrazole 4 wass hown in 1909 by Schroeter, andl ater confirmedb yG çtzky (Scheme2B). [16] Subsequent studieso nt he thermolysiso fg eminald iazidesb yMoriarty andc o-workersd escribed tetrazolef ormation with af ew diazidomalonic acid derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…During our ongoing studies on the synthesis and reactivity of compounds with geminal diazido units, we observed that tetrazole formation can be easily triggered with this still barely known compound class: Diazido esters (e.g., 1 ) were smoothly converted into the corresponding tetrazoles through simple treatment with triethylamine as base additive (Scheme A) . We then questioned whether a universal approach to the tetrazole core may exist, starting from geminal diazide substrates, and deliberately different from the classical cycloaddition with nitriles and azides.…”
Section: Introductionmentioning
confidence: 99%